Application of high-performance liquid chromatography with electrochemical detection for the analysis of N-(1,3-dimethylbutyl)-N’-phenyl-p-phenylenediamine quinone in ambient particulates - Natsumi Okawa; Akira Ito; Vonika Ka-Man Au; Nozomu Tsuchiya; Takayuki Kameda (Journal of Chromatography Open)
A simple and sensitive high-performance liquid chromatography (HPLC) method with electrochemical detection (ECD) was developed for measuring N-(1,3-dimethylbutyl)-N’-phenyl-p-phenylenediamine quinone (6-PPDQ) in environmental samples. The system used C30 columns for sample separation and a dual-mode electrochemical detector with a reduction cell, followed by an oxidation/detection cell connected in series. Under the optimal reduction voltage (–600 mV vs. Au) and optimal oxidation voltage (+600 mV vs. Ag/AgCl), the assay demonstrated high accuracy (96 %–107 %) when applied to airborne particulate sample extracts spiked with known amounts of 6-PPDQ. The detection limit was 3 fmol per injection (signal-to-noise ratio = 3), with a calibration range of 0.1–100 pmol, exhibiting excellent linearity (R2 > 0.9995). Using this newly developed HPLC-ECD analytical method with simple sample preparation, daily variations in 6-PPDQ concentrations in airborne particles collected in Kyoto, Japan, ranging from 21 to 165 fmol m–3 (n = 20), were successfully measured, highlighting the high potential of this HPLC-ECD method for routine trace analysis in environmental samples.